(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s
(3ChdgG (B:s
(3hEP bO PcQfG ai GdebGdJjf GdChdjjf bHd gPG GdWQjb GdPi jSdc ajg Edi GdeOGhGg ef GdCeQGV hGdYdd s
(3BNQgG (B:s
(3aGeG GddYGHGJ GdJi JSjd ef CahGg adjSeM Gdae bO fbY ai TQGH aEfg jbWYg aEYde Pdc Ef TGA Gddg JeJ GdebGdI GdNGeSI s
(3bWYI JTJed Ydi GdebGdI GdNGeSI ef GdLRA GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B153 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1380s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeYI GdCeQjcjI (B/ (3HjQhJ (B((3GdbSe GdLOjO (B43) s
Keywords: (3GdWHs